Escola, fam??lia e a ocorr??ncia de bullying em uma escola com disciplina militar - Ara??jo, Maria Abadia Machado (2016)
This is a qualitative study on the role of school and family in identifying Bullying occurrence in a military school in Bras??lia, Brazil. It aims to understand how teenagers perceive their relationship to family and school and Bullying occurrence in their school. Theoretical basis was Systemic Structural Theory and some other researchers on the theme. The subjects surveyed were four students from the 9th grade of elementary school, aged 13 to 15 years, who passed through the School Guidance Service and a history of involvement with bullying, as victims, as aggressors or as spectators. None of them had previous direct contact with the researcher. For data collection, we used two instruments: a documental analysis script in the School Guidance Service aiming to identify cases of bullying and a semi-structured interview script. Initially we carried out a survey on the students' records and asked parents by telephone to authorize their children to participate in the research. Afterwards we scheduled individual interviews to the students, which lasted, on average, an hour. To analyze the data, we employed Gonz??les Rey???s qualitative epistemology and we raised indicators that allowed to propose four zones of sense. We called the first one as Occurrence of Bullying in Military School of Brasilia. This zone describes the surveyed students and their perception on bullying occurrence in the school, as well their concepts and feelings concerning to bullying. In this zone, he results pointed out that all the subjects unanimously have identified bullying cases in the school context and all of them reported having experienced situations characteristics of bullying. In their opinion, these situations occur in the recess, in the intervals and in the Physical Education classes. Most of the surveyed students report that the aggressors are often older than the victim. They consider s bullying any form of violence occurred in the school. The second zone was named Family model of Military School of Brasilia in which we sought to identify how adolescents perceive values, rules, roles and authority in their family context. He results showed that the family has deep influence in the teenager formation and decision making. Hey reported a good relationship to their parents. In the families, there is a division of tasks between all the members. The adolescents also demonstrated to live with the reality of limits in a very natural way, in matters such as asking permission to leave home schedules, discipline and their report allowed us to conclude that they are functional families. In the third zone, Partnership family-school, we sought to understand the relationship between the families and the school and their attitude against bullying, the establishment of rules and authority in both institutions. The students reported a harmonic relationship between the two institutions. They said that sometimes there are problems but parents and school solve together and everyone gains with new learning. They unanimously reported punishments both in school and in family e and they deal well with this situation. Finally, the fourth zone Discipline and limits are important to our future, aimed to know the expectations of the students related to the disciplinary and pedagogical model of the surveyed school. Developing a conscientious discipline with moral and ethical values, clear and well established rules, limits and authority was considered as positives aspects. They reported that these issues are important for their professional formation and for a better future. Their positions reinforce that it is essential that the school develops the competences related to teaching, but also healthy habits of behavior and discipline. The research allowed us to reflect on the urgency of the partnership between school and family to achieve the social wellbeing of all the involved people.